Evaluating User Satisfaction and Public Engagement in Local Government Social Media - Aman, Azwar; Imtihan, Khairul; Rodi, Muhamad (International Journal of Engineering, Science and Information Technology, 2025)
Through an integrated model, this study investigates the determinants of user satisfaction, trust, engagement, and continuance intention in local government social media. While social media has become a vital tool for digital governance, its adoption in semi-urban regions often encounters institutional and behavioral challenges. To address this gap, this research develops and validates a framework combining the Technology Acceptance Model (TAM), the E-Government Adoption Model (e-GAM), and the Importance-Performance Map Analysis (IPMA). Using a quantitative approach and PLS-SEM via SmartPLS 4.0, data from 355 respondents in Central Lombok Regency, Indonesia, were analyzed across eleven constructs, including perceived usefulness, ease of use, Transparency, interaction, digital literacy, and trust. Results show that Transparency, Interactivity, and digital literacy significantly impact user satisfaction, whereas traditional TAM factors were insignificant. User satisfaction strongly influenced both public engagement and continuance intention. The IPMA findings highlight Transparency and Interactivity as high-priority areas for improvement. These results underline the importance of institutional attributes in shaping digital public engagement, particularly in developing contexts.